PERENCANAAN STRATEGIS SISTEM INFORMASI PADA SEKOLAH MENENGAH ATAS DENGAN METODE WARD AND PEPPARD - Evy Nurmiati; Cut Aja Anis Layyinna; Musthafa Kamil (JURSIMA (Jurnal Sistem Informasi dan Manajemen), 2022)
With the rapid development of technology and information systems, every organization should register information systems on their mandatory agenda, including schools. SMAN 2 Sekayu is one of the favorite high schools in Musi Banyuasin Regency, South Sumatra, but this school does not yet have an information system to manage their business processes. This study aims to carry out strategic planning of information systems that can be used as a reference in developing information systems that manage school business processes. By using the Ward & Peppard approach, the data collection methods used include literature study, observation, and interviews. Meanwhile, the data analysis methods used include PEST, Value Chain, and SWOT analysis. The results of this study are recommendations for information system applications that are mapped using the McFarland Strategic Grid which can be used as a reference for SMAN 2 Sekayu in developing their information system.